Tomato Breeding for Sustainable Crop Systems: High Levels of Zingiberene Providing Resistance to Multiple Arthropods - João Ronaldo Freitas de Oliveira; Juliano Tadeu Vilela de Resende; Renato Barros de Lima Filho; Sergio Ruffo Roberto; Paulo Roberto da Silva; Caroline Rech; Cristiane Nardi (Horticulturae, 2020)
In sustainable cropping systems, the management of herbivorous arthropods is a challenge for the high performance of the tomato crop. One way to reduce the damage caused by these pests is the use of resistant cultivars within a sustainable integrated management system. The host selection of Tetranychus urticae, Bemisia tabaci, and Tuta absoluta was evaluated, characterizing their preference among the tomato genotypes RVTZ2011-79-503-143, RVTZ2011-79-335-164, RVTZ2011-79-185-250 (high zingiberene content—HZC), and RVTZ2011-79-117-273 (low zingiberene content—LZC). Such genotypes were selected in the F2BC2 generation (the F2 generation of the 2th backcross towards Solanum lycopersicum after the inicial interspecific cross S. lycopersicum × S. habrochaites var. hirsutum), resulting from crossing Solanum habrochaites var. hirsutum PI-127826 (HZC and resistant to mites) and the commercial cv. Redenção (S. lycopersicum) (LZC and susceptible to mites). In choice and no-choice bioassays by T. urticae, and in choice bioassays by B. tabaci and T. absoluta, arthropods preferred to stay and oviposit in an LZC genotype. In contrast, genotypes with HZC showed repellency to pests and induced a non-preference for oviposition. The F2BC2 genotypes selected for HZC are considered sources of resistance genes to these pests for tomato breeding programs, and therefore have excellent potential for sustainable cropping systems. These results represent an advance in obtaining tomato genetic materials which can be used in sustainable production systems with less loss from pests.